The Relation of Articulatory and Vocal Auditory--Motor Control in Typical Speakers. - Lester-Smith, Rosemary A.; Daliri, Ayoub; Enos, Nicole; Abur, Defne; Lupiani, Ashling A.; Letcher, Sophia; Stepp, Cara E. (Journal of Speech, Language & Hearing Research, 2020)
Purpose: The purpose of this study was to explore the relationship between feedback and feedforward control of articulation and voice by measuring reflexive and adaptive responses to first formant (F) and fundamental frequency (f) perturbations. In addition, perception of F and f perturbation was estimated using passive (listening) and active (speaking) just noticeable difference paradigms to assess the relation of auditory acuity to reflexive and adaptive responses. Method: Twenty healthy women produced single words and sustained vowels while the F or f of their auditory feedback was suddenly and unpredictably perturbed to assess reflexive responses or gradually and predictably perturbed to assess adaptive responses. Results: Typical speakers' reflexive responses to sudden perturbation of F were related to their adaptive responses to gradual perturbation of F. Specifically, speakers with larger reflexive responses to sudden perturbation of F had larger adaptive responses to gradual perturbation of F. Furthermore, their reflexive responses to sudden perturbation of F were associated with their passive auditory acuity to F such that speakers with better auditory acuity to F produced larger reflexive responses to sudden perturbations of F. Typical speakers' adaptive responses to gradual perturbation of F were not associated with their auditory acuity to F. Speakers' reflexive and adaptive responses to perturbation of f were not related, nor were their responses related to either measure of auditory acuity to f. Conclusion: These findings indicate that there may be disparate feedback and feedforward control mechanisms for articulatory and vocal error correction based on auditory feedback.